Praxeology and Space Syntax: - Adriano Paranaiba (Mises, 2018)
The purpose of this paper is to identify the Praxeology as a method for studies that aim to bring solutions to urban mobility. In these sense, the present article seeks to connect Praxeology with the Theory of Space Syntax. For the Theory of Space Syntax understands urban spaces as a product of human interactions, and these are treated by the individual logic of their interests, and human dynamics within urban areas that may differ from what was originally planned.